Influence of opioid peptides on human neutrophil apoptosis and activation in vitro. - Sulowska, Zofia (2002)
BACKGROUND: It has been shown that cells of the immune system release opioid peptides and possess receptors for them. The concentrations of opioid peptides in the peripheral circulation rapidly increase during inflammation and acute stress response. AIMS: The effect of opioid peptides Met-enkephalin (M-ENK) and beta-endorphin (beta-END) on the oxidative metabolism of normal human neutrophils and their death by apoptosis in vitro was investigated. METHODS: Isolated from peripheral blood, neutrophils were incubated in the presence or absence of 10(-6) to 10(-10) M of M-ENK and beta-END for 12 and 18 h. Apoptosis of neutrophils was determined in vitro by flow cytometric analysis of cellular DNA content and Annexin V-FITC protein binding to the cell surface. The MTT-reduction assay was employed to estimate the oxidative metabolism of neutrophils. RESULTS: Treatment with M-ENK caused a significant increase in apoptotic cells after 18 h of culture: *0 M (control) versus 10(-10) M, p < or = 0.02; **10(-10) M versus 10(-10) M, p < or = 0.02. Treatment with beta-END caused a significant increase in apoptotic cells after 12 h of culture: 0 M versus 10(-8) M, p < or = 0.03; **0 M versus 10(-10) M, p < or = 0.04. We found the significant increase in MTT reduction by neutrophils in the presence of M-ENK and beta-END both before and after the culture. However, the ability of neutrophils to reduce the MTT salt to formazan decreased significantly after the culture. CONCLUSIONS: We observed that the in vitro effect of opioid peptides on the neutrophil survival and their functional state was time and dose dependent. The presence of antioxidants in the culture medium modifies neutrophil survival.